Self-assembling tyrosine kinase inhibitors for localised targeted delivery - Al-Ameedee, Mohammed (2017)
Localised delivery of cancer therapy is an approach used to overcome the serious side effects associated with the systemic treatment of many anticancer drugs which is the main route of administration. Low molecular weight gelators have received great attention in recent years as a drug delivery strategy for localised targeted therapy. These are small molecules, which self-assemble into a 3D network fibre via non-covalent interactions to create macroscopically a gel. Studies on this drug delivery platform provide an alternative to the extensively investigated gel delivery systems based on polymers. One of the approaches of low molecular weight gelators is the development of gelators based on anticancer drugs, i.e. self-assembled anticancer prodrug gelators that form a gel. Indeed, there are only a limited number of studies which investigate the gelation ability of anticancer drugs. Therefore, this project intends to search for an anticancer agent which demonstrates gelation. This has been achieved by preliminary screening of selected members of two categories of cancer treatments which are five benzothiazole-based quinols and four tyrosine kinase inhibitors (sorafenib, linifanib, semaxanib and orantinib). These anticancer drugs have significant anticancer activity but suffer from systemic toxicity. Therefore, the development of LMWGs based on these drugs is a useful approach for localised drug delivery helping improve the toxicity profile. Preliminary screening showed that only linifanib out of the compounds investigated formed gels. Therefore, it was decided to focus on this potent tyrosine kinase inhibitor as the main part in this project. Further characterisation and analysis showed that the urea functional group and the fluorine substitution on the adjacent aromatic ring are key elements in promoting self-assembly. Also, oscillatory rheology showed that linifanib has superior mechanical strength to gels of structurally related analogues. The prodrug approach was then progressed with linifanib to provide more controlled delivery of the drug. The first library of potential linifanib prodrugs were carbamate derivatives. Unfortunately, all of these compounds failed in inducing gel formation in the preliminary screening regardless of the length and nature of side chain. The second linkage used for creating linifanib prodrugs was the amide conjugation with aliphatic carboxylic acids, single amino acid and dipeptides. With regard to the derivatives with aliphatic carboxylic acid side chain, gels were formed for compounds with clog P between 3.98 and 4.72 which means that there is a correlation between hydrophobicity and gel formation. Preliminary screening of dipeptide derivatives of linifanib were negative for all compounds except the proline-proline derivative which formed a gel after 7 days. Stability study in DMSO – water mixtures of these compounds showed that proline-containing dipeptides degraded to linifanib, at a quicker cleavage rate than other compounds, with the highest cleavage rate for the proline-proline analogue. This has led to the conclusion that the gel observed for this analogue was due to the gelation of linifanib. Finally, the single amino acid derivatives gelation screening revealed that the serine analogue of linifanib was the most stable gel. Further characterisation of this compound showed that the formation of gel and its mechanical strength are affected mainly by changes in pH and possibly the buffer composition. The highest mechanical strength was observed with the concentration of 0.5% w/v serine analogue in 5% v/v DMSO/phosphate buffer pH 7.4. Overall, the serine analogue of linifanib can be considered as the best gelator prodrug of linifanib for two main reasons. This derivative exhibited stable gels with good mechanical strength (> 4 kPa) at physiologic pH. In addition, the serine derivative of linifanib demonstrated a cleavage rate half-life of 7 days in phosphate buffer pH 7.4. These findings suggest that it is a promising linifanib prodrug gelator for targeted delivery.